Abstracts published in the Proceedings of the Jaffna Science Association (1992-2017): A bibliometric analysis - Tharsiny, M.; Chandrasekar, K. (Jaffna Science Association, 2020)
Bibliometrics offers a powerful set of methods and measures for studying the structure and process of scholarly communication. By employing bibliometric approach, this paper examines the characteristics of the abstracts published in the Proceedings of the Jaffna Science Association (JSA), covering a 25-year period. Bibliographical details of 893 abstracts available in 24 volumes of the JSA proceedings were collected, tabulated, analyzed and reported. The attributes such as, distribution of abstracts, authorship pattern, institutional contribution, medium of language, subject coverage, and format of the abstracts were taken into consideration for the bibliometric analysis. Results showed that there is variation in the number of abstracts published per year, ranging from 17 to 74. Besides, 72.79% of the published abstracts belonged to pure and applied sciences. Collaborative authorship is a prominent feature observed in 81.52% of the abstracts, which is the current trend in scholarly communication. Among the contributing institutions, University of Jaffna is at the forefront. Analysis of subject coverage revealed that 62.71% of the abstracts related to the disciplines namely agriculture, biology and biochemistry. In view of enhancing the accessibility, majority of the authors selected English as a channel for their scholarly communication. Furthermore, it was found that 78.72% of the abstracts comply with the guidelines for the abstract layout, prescribed by the JSA. Regarding the length of abstracts, 44.46% fall within the acceptable range of 200- 299 words. This bibliometric study of scholarly communication provided a comprehensive view of the dynamical growth of knowledge of the region.
Keywords: Bibliometrics; Scientific production; Bibliometry; Scholarly publications; Bibliometric analysis